Análisis iconográfico de los petroglifos geométricos ubicados en el río Anzú y Piatua del valle sagrado, provincia de Napo - Caminos Calles, Adriana Rashel (2022)
The Antsuk Rumi petroglyph was named by the authorities of the Carlos Julio Arosemena Tola canton, located in the community of El Capricho belonging to the province of Napo, being the province with the largest number of petroglyphs and the territory where pre-Columbian communities such as the Omaguas inhabited, whose legacy is summarized in semi-forgotten stories and abandoned monuments despite having been an advanced Amazonian indigenous society within the period of integration. One of its elements that are preserved to this day is the petroglyph that contains engravings of figures, linear shapes and most importantly its ideology, these elements present in the petroglyph indicate the social guidelines that were part of the community. Their harmony with nature allowed them to replicate a colossal volcano in a stone that became their center of symbolic representation. Beyond their laws and ways of life, as Oberem mentions in his stories, they were victims of Spanish colonization, although they became the first indigenous people to have contact with them, this knockout them to be part of the end of their community, because the new ideology of extermination implanted by the settlers led them to determine their destiny as people.